Practical validation framework for competence measurement in VET: a validation study of an instrument for measuring basic commercial knowledge and skills in Switzerland - Rohr-Mentele, Silja [Verfasser]; Forster-Heinzer, Sarah [Verfasser] (My University, 2021)
“Competence development and measurement are of great interest to vocational education and training (VET). Although there are many instruments available for measuring competence in diverse settings, in many cases, the completed steps of validation are neither documented nor made transparent in a comprehensible manner. Understanding what an instrument actually measures is extremely important, inter alia, for evaluating test results, for conducting replication studies and for enforcing adaptation intentions. Therefore, more thorough and qualitative validation studies are required. This paper presents an approach to facilitate validation studies using the example of the simuLINCA test. The approach to validation applied in this study was developed in the field of medicine; nevertheless, it provides a promising means of assessing the validity of (computer-based) instruments in VET. We present the approach in detail along a newly developed computer-based simulation (simuLINCA) that measures basic commercial knowledge and skills of apprentices in Switzerland. The strength of the presented approach is that it provides practical guidelines that help perform the measurement process and support an increase in transparency. Still, it is flexible enough to allow different concepts to test development and validity. The approach applied proved to be practicable for VET and the measurement of occupational competence. After extending and slightly modifying the approach, a practical validation framework, including the description of each step and questions to support the application of it, is available for the VET context. The computer-based test instrument, simuLINCA, provides insights into how a computer-based test for measuring competence in various occupational fields can be developed and validated. SimuLINCA showed satisfying evidence for a valid measurement instrument. It could, however, be further developed, revised and extended. “ (authors‘ abstract; BIBB-Doku)
Keywords: L 6.3.1 Diagnose- & Messinstrumente; S 6.4.1 Kaufleute; I 2.2.1 Westeuropa; 370; Kompetenzentwicklung; Kompetenzfeststellung; Anerkennung; Kaufmännische Bildung; Auszubildender; Schweiz